2008
DOI: 10.1074/jbc.m804817200
|View full text |Cite
|
Sign up to set email alerts
|

A Drosophila Model for Amyotrophic Lateral Sclerosis Reveals Motor Neuron Damage by Human SOD1

Abstract: Amyotrophic lateral sclerosis (ALS) is a motor neuron disease that leads to loss of motor function and early death. About 5% of cases are inherited, with the majority of identified linkages in the gene encoding copper, zinc-superoxide dismutase (SOD1). Strong evidence indicates that the SOD1 mutations confer dominant toxicity on the protein. To provide new insight into mechanisms of ALS, we have generated and characterized a model for familial ALS in Drosophila with transgenic expression of human SOD1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
128
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(144 citation statements)
references
References 64 publications
13
128
2
1
Order By: Relevance
“…Motoneuron GAL4 driver lines were: (1) w; P103.3-GAL4, UAS-mCD8-GFP;+, (2) C380-GAL4, UAS-mCD8-GFP;; Cha-GAL80 and (3) w;UAS-mCD8-GFP; D42-GAL4, Cha-GAL80. All express in a subset of motoneurons including MN5, but also in some non-identified sensory neurons and interneurons (Yeh et al, 1995;Sanyal et al, 2003;Sanyal, 2009;Budnik et al, 1996;Consoulas et al, 2002;Watson et al, 2008). The Cha-GAL80 transgene was included to inhibit expression in non-identified cholinergic sensory neurons and interneurons.…”
Section: Animalsmentioning
confidence: 99%
“…Motoneuron GAL4 driver lines were: (1) w; P103.3-GAL4, UAS-mCD8-GFP;+, (2) C380-GAL4, UAS-mCD8-GFP;; Cha-GAL80 and (3) w;UAS-mCD8-GFP; D42-GAL4, Cha-GAL80. All express in a subset of motoneurons including MN5, but also in some non-identified sensory neurons and interneurons (Yeh et al, 1995;Sanyal et al, 2003;Sanyal, 2009;Budnik et al, 1996;Consoulas et al, 2002;Watson et al, 2008). The Cha-GAL80 transgene was included to inhibit expression in non-identified cholinergic sensory neurons and interneurons.…”
Section: Animalsmentioning
confidence: 99%
“…As useful as these have been, mouse models do have some drawbacks: the mice are highly inbred, which may affect the disease progression and phenotypes; some lines express very high levels of mutant protein, which may not accurately reflect the human situation; and it is expensive to perform drug screens in mice. Drosophila and C. elegans that overexpress human SOD1 mutations have also been generated (Mockett et al, 2003;Oeda et al, 2001;Watson et al, 2008). These animals do recapitulate some ALS phenotypes in that they show motoneuron damage (Watson et al, 2008), however, they do not display motoneuron loss, paralysis or premature death.…”
Section: Introductionmentioning
confidence: 99%
“…Drosophila and C. elegans that overexpress human SOD1 mutations have also been generated (Mockett et al, 2003;Oeda et al, 2001;Watson et al, 2008). These animals do recapitulate some ALS phenotypes in that they show motoneuron damage (Watson et al, 2008), however, they do not display motoneuron loss, paralysis or premature death. To complement these models and to generate a vertebrate model of ALS that may be more amenable to cellular manipulation and to drug or genetic screening, we have generated zebrafish that carry mutant forms of Sod1.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, subsequent studies in transgenic fly model, overexpressing human WT SOD1 only in motor neurons, showed an extension of lifespan, without affecting locomotion or motor neuron survival (Parkes, et al, 1998). In contrast, another study showed that selective expression of WT or human SOD1 (hSOD1) diseaselinked (A4V, G85R) mutants in motor neurons induced progressive motor dysfunctions, coupled with electrophysiological defects and abnormal accumulation of the protein and a stress response in surrounding glial cells (Watson, et al, 2008). These effects were accompanied by synaptic transmission deficits, focal accumulation of hSOD1 in motor neurons, and up-regulation of heat shock protein in glia.…”
Section: Drosophila Sod1 Modelsmentioning
confidence: 99%